Exploring the Reduction in Childhood Undernutrition in Morocco (2003–2018): Insights From a Decomposition Analysis - Berrouyne, Mustapha; Hami, Hinde (Journal of Population and Social Studies [JPSS], 2025)
Despite significant progress, childhood undernutrition remains a critical public health challenge in Morocco, impacting child development and well-being. This study examines the drivers behind the reduction in undernutrition between 2003 and 2018, employing multilevel logistic regression and Fairlie decomposition analysis to assess the influence of socioeconomic, demographic, and contextual factors. Using data from the 2003–2004 and 2018 National Survey on Population and Family Health (NSPFH), the findings underscore the pivotal roles of improved maternal education, enhanced child healthcare access, and better household living conditions, including access to clean water and sanitation. However, rural areas lag significantly behind their urban counterparts, highlighting persistent regional disparities that demand urgent attention. These results underline the critical need for targeted interventions to advance maternal education, strengthen healthcare infrastructure, and prioritize rural development. This study highlights past achievements by aligning with long-term development objectives and global health initiatives. It provides actionable insights to sustain and accelerate reductions in childhood undernutrition in Morocco.